Business Model Innovation : From Systematic Literature Review to Future Research Directions - Andreini, Daniela; Bettinelli, Cristina (International series in advanced management studies., 2017)
This book presents a systematic literature review of 156 published papers on business model innovation (BMI). The aim is to identify and integrate the different theoretical perspectives, analytical levels, and empirical contexts in order to deepen understanding of this complex phenomenon. The authors conduct an inductive thematic analysis based on an informal ontological classification that identifies 56 key themes. Within each theme, discussion focuses on thematic patterns, potential inconsistencies and debates, and future directions and opportunities for research. The book makes a number of significant contributions to the field. First, it offers a deeper understanding of the evolution of research on BMI through an ontological map that identifies the key thematic areas in the literature. Second, a multilevel model is developed that clarifies the concept of BMI by identifying its drivers, contingencies, and outcomes. Third, the authors identify clear and specific directions for further research and offer suggestions on research design, creating an informative road map for the future. The book will be of value both to scholars and researchers and to practitioners.